Criminal Acts of Narcotics Abuse for Oneself Based on Law Number 35 of 2009 Concerning Narcotics - Purwoko, Purwoko; Mandasari Saragih, Yasmirah (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
The existence and use of narcotics are legal in terms of legal aspects. Law Number 35 of 2009 concerning Narcotics only prohibits the use of narcotics not in accordance with the provisions of the law or referred to as drug abuse. Drug abuse for oneself is seen as a perpetrator of a crime as well as a victim, based on this, the sanctions that will be applied to drug abuse for oneself must be taken through rational policies.